Gene variants previously associated with reduced soft tissue injury risk: Part 1 - independent associations with elite status in rugby - Brazier, J.; Antrobus, M. R.; Herbert, A. J.; Callus, P. C.; Stebbings, G. K.; Day, S. H.; Heffernan, S. M.; Kilduff, L. P.; Bennett, M. A.; Erskine, R. M.; Raleigh, S. M.; Collins, M.; et al. (European Journal of Sport Science, 2023)
There is growing evidence of genetic contributions to tendon and ligament pathologies. Given the high incidence and severity of tendon and ligament injuries in elite rugby, we studied whether 13 gene polymorphisms previously associated with tendon/ligament injury were associated with elite athlete status. Participants from the RugbyGene project were 663 elite Caucasian male rugby athletes (RA) (mean (standard deviation) height 1.85 (0.07) m, mass 101 (12) kg, age 29 (7) yr), including 558 rugby union athletes (RU) and 105 rugby league athletes. Non-athletes (NA) were 909 Caucasian men and women (56% female; height 1.70 (0.10) m, mass 72 (13) kg, age 41 (23) yr). Genotypes were determined using TaqMan probes and groups compared using Chi2 and odds ratio (OR). COLGALT1 rs8090 AA genotype was more frequent in RA (27%) than NA (23%; P = 0.006). COL3A1 rs1800255 A allele was more frequent in RA (26%) than NA (23%) due to a greater frequency of GA genotype (39% vs 33%). For MIR608 rs4919510, RA had 1.7 times the odds of carrying the CC genotype compared to NA. MMP3 rs591058 TT genotype was less common in RA (25.1%) than NA (31.2%; P < 0.04). For NID1 rs4660148, RA had 1.6 times the odds of carrying the TT genotype compared to NA. It appears that elite rugby athletes have an inherited advantage that contributes to their elite status, possibly via resistance to soft tissue injury. These data may, in future, assist personalised management of injury risk amongst athletes.